Comparison between telephone and self-administration of Short Form Health Survey Questionnaire (SF-36) Estudio comparativo entre la encuesta telefónica y la autoaplicada del cuestionario de salud SF-36 - María García; Izabella Rohlfs; Joan Vila; Joan Sala; Araceli Pena; Rafael Masiá; Jaume Marrugat (Elsevier, 2005)
Objective: The characteristics of the 36 item Medical Outcome Short Form Health Study Survey (SF-36) questionnaire, designed as a generic indicator of health status for the general population, allow it to be self-administered or used in personal or telephone interviews. The main objective of the study was to compare the telephone and self-administered modes of SF-36 for a population from Girona (Spain). Methods: A randomized crossover administration of the questionnaire design was used in a cardiovascular risk factor survey. Of 385 people invited to participate in the survey, 351 agreed to do so and were randomly assigned to two orders of administration (i.e., telephone-self and self-telephone); 261 completed both questionnaires. Scores were compared between administration modes using a paired t test. Internal consistency and agreement between modalities were analyzed by respectively applying Chronbach's alpha and intraclass correlation coefficients. The effect of the order of administration on the test-retest difference was analyzed by one-way ANOVA for repeated measurements. Results: Physical function, physical role and social functioning received significantly lower scores when the self-administered questionnaire was used prior to the telephone survey. When the initial survey was conducted by telephone, all Chronbach's alpha coefficients (except social functioning) scored over 0.70 in the self-administered modality. The intraclass correlation coefficient ranged from 0.41 to 0.83 for the telephone-self order and from 0.32 to 0.73 for the self-telephone order. No clinically significant effect was observed for the order of application. Conclusions: The results of the present study suggest that the telephone-administration mode of SF-36 is equivalent to and as valid as the self-administered mode. Objetivo: El cuestionario de salud SF-36 puede ser autoaplicado o utilizado en entrevistas personales o telefónicas. El objetivo principal de este trabajo fue comparar la aplicación telefónica del cuestionario y la versión autoaplicada en una población de Girona (España). Métodos: Diseño cruzado y aleatorizado para la aplicación de las dos formas del cuestionario. Se asignaron dos órdenes de aplicación de las encuestas (telefónica-autoaplicada y autoaplicada-telefónica). Un total de 261 personas completaron los cuestionarios. Las comparaciones entre modos de aplicación se realizaron mediante la prueba de la t de Student para datos apareados. La consistencia interna y la concordancia entre modos de aplicación se analizaron mediante los coeficientes * de Chronbach y de correlación intraclase, respectivamente. Su utilizó un modelo lineal general para medidas repetidas para evaluar el efecto del orden de la aplicación de los cuestionarios. Resultados: Cuando se utilizó primero el cuestionario autoaplicado, las escalas de función física, rol físico y función social resultaron en una menor puntuación. Todos los coeficientes * de Chronbach fueron superiores a 0,70, excepto para la escala de función social en la modalidad autoaplicada cuando se aplicó primero la encuesta telefónica. El rango de los coeficientes de correlación intraclase fue de 0,41 a 0,83 en la modalidad telefónica-autoaplicada y de 0,32 a 0,73 en la modalidad autoaplicada-telefónica. No se observó un efecto relevante del orden de aplicación.